PENDAMPINGAN PAMERAN TAMAN BACA KREATIF DI TAMAN ISMAIL MARZUKI - Setiawan, M. Nashir (Jurnal Serina Abdimas, 2023)
Participating in exhibitions for small communities that do not yet have a permanent venue and limited equipment is a joy and a positive motivation for members and managers. The Creative Reading Garden was founded on November 1 2022, in fact it has been active since 2019, however, it was only started to create a Reading Garden after receiving enlightenment and technical instructions from Community Reading Center (TBM) activists and North Jakarta TBM Coordinator, Acbar Dheny, S.E. Some of the things that have become a strong motivation for the establishment of this Creative Reading Garden are that it has regular activities, there are works that are documented, there are permanent members in the environment and there are managers who continuously carry out activities. TBM is a forum to encourage community growth to fulfill non-formal education, aiming to increase people's interest in reading so that they have broad knowledge. However, changing people who are not used to reading to become fond of reading is not an easy matter. Therefore, the activities carried out are with an approach to children who are interested in drawing activities. Through the drawing activities that were carried out, the benefits began to be felt, some participants became more proficient in coloring, shaping or imitating pictures. Apart from drawing, other activities were included, such as singing folk songs, storytelling and reading books aloud (Read Load). In the Read Load practical activity, new writers know how important it is to read story books aloud to children, with certain methods to make children pay attention and understand the contents of the story. This is evidenced by several children being asked to retell stories and being able to tell stories coherently. TB Creative's participation in this event strengthens motivation to be able to continue to encourage the surrounding community to love reading. The availability of Creative Reading Parks in Bulak Simpul increases interest in reading and increases creativity in children, with the development of a reading culture through Creative Reading Gardens that are limited to site conditions. Mengikuti kegiatan pameran bagi komunitas kecil yang belum memiliki wadah tetap dan serba terbatas peralatannya adalah hal yang menggembirakan dan menjadi motivasi positif bagi anggota dan pengelola. Taman Baca Kreatif berdiri tanggal 1 November 2022 ini, sebenarnya telah beraktifitas sejak tahun 2019, namun demikian baru terbetik untuk dibuat Taman Baca setelah mendapat pencerahan dan petunjuk teknis dari pegiat Taman Bacaan Masyarakat (TBM) dan Koordinator TBM Jakarta Utara, Acbar Dheny, S.E. Beberapa hal yang menjadi motivasi kuat berdirinya Taman Baca Kreatif ini adalah telah berkegiatan secara rutin, ada karya yang didokumentasikan, terdapat anggota tetap di lingkungan tersebut serta ada pengelola yang secara kontinyu menjalankan kegiatan. TBM merupakan suatu wadah untuk mendorong tumbuhnya masyarakat memenuhi pendidikan nonformal, bertujuan meningkatkan minat baca masyarakat sehingga memiliki pengetahuan yang luas. Namun demikian, mengubah masyarakat yang tidak biasa membaca menjadi gemar membaca bukan persoalan mudah. Oleh karena itu, kegiatan yang dilakukan adalah dengan pendekatan pada anak-anak yang tertarik kegiatan menggambar. Melalui kegiatan menggambar yang dilakukan, mulai terasa manfaatnya, beberapa peserta menjadi lebih cakap dalam mewarnai, membentuk atau mencontoh gambar. Selain menggambar kegiatan lain disisipkan seperti menyanyi lagu-lagu daerah, mendongeng dan membaca buku dengan nyaring (Read Load). Pada kegiatan praktek Read Load, penulis baru mengetahui betapa penting membacakan buku cerita dengan keras pada anak-anak, dengan metode tertentu menjadikan anak-anak perhatian serta memahami isi cerita. Ini dibuktikan dengan beberapa anak-anak diminta menceritakan kembali cerita dan bisa bercerita secara runtut. Keikutsertaan TB Kreatif pada event ini memperkuat motivasi untuk dapat terus mendorong masyarakat sekitar untuk gemar membaca. Ketersediaan Taman Baca Kreatif di Bulak Simpul meningkatkan minat baca dan meningkatkan kreativitas pada anak-anak, dengan pengembangan budaya baca melalui Taman Baca Kreatif memiliki keterbatasan pada kondisi lokasi.